Involvement of miR-30c in resistance to doxorubicin by regulating YWHAZ in breast cancer cells - Fang,Y. (2014)
MicroRNAs (miRNAs) are small RNA molecules that modulate gene expression implicated in cancer, which play crucial roles in diverse biological processes, such as development, differentiation, apoptosis, and proliferation. The aim of this study was to investigate whether miR-30c mediated the resistance of breast cancer cells to the chemotherapeutic agent doxorubicin (ADR) by targeting tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein zeta (YWHAZ). miR-30c was downregulated in the doxorubicin-resistant human breast cancer cell lines MCF-7/ADR and MDA-MB-231/ADR compared with their parental MCF-7 and MDA-MB-231 cell lines, respectively. Furthermore, we observed that transfection of an miR-30c mimic significantly suppressed the ability of MCF-7/ADR to resist doxorubicin. Moreover, the anti-apoptotic gene YWHAZ was confirmed as a target of miR-30c by luciferase reporter assay, and further studies indicated that the mechanism for miR-30c on the sensitivity of breast cancer cells involved YWHAZ and its downstream p38 mitogen-activated protein kinase (p38MAPK) pathway. Together, our findings provided evidence that miR-30c was one of the important miRNAs in doxorubicin resistance by regulating YWHAZ in the breast cancer cell line MCF-7/ADR.